STUDI TINGKAT KEBERHASILAN TANAMAN REHABILITASI HUTAN DAN LAHAN (RHL) KELOMPOK TANI HUTAN SEMIDANG GUMAY - Syaefudin, M Wahid; Rahmatia, Citra; Kurniawan, Riko (LPPM Universitas Muhammadiyah Jambi, 2024)
Indonesia has forest areas and there has been pressure from forest and land degradation. In order to control the rate of forest and land destruction, efforts are being made, namely rehabilitation. This study aims to determine the level of success of forest and land rehabilitation by looking at the level of plant growth carried out in the Semidang Gumay Forest Farmer Group, in August-September 2024. This study uses the Systematic Sampling with Random Start method which is carried out through sampling techniques. The results of this study indicate that (1) Plant Assessment with the number of plants that should be in 13 measuring plots is 520, while in fact the number of plants in the 13 measuring plots is 462 plants there are 429 living plants and 33 dead plants (2) It is known that the largest number of living plants is in measuring plot 4 with 40 living plants so that the plant growth percentage is 100%. Meanwhile, the smallest number of plants were found in plots 5, 7 and 10 with 30 living plants with 75% plant growth (3). The recapitulation of the results shows that the average percentage of plant growth was 82.5%.